KNOWLEDGE OF PREGNANT MOTHER ABOUT COVID-19 VACCINE ON THE PARTICIPATION RATE OF PREGNANT MOTHERS IN THE COVID-19 VACCINATION PROGRAM - Tety Ripursari; Dyah Ernawati (Journal for Quality in Women's Health, 2022)
ABSTRACT Background : Indonesia has made the implementation of the corona virus vaccination part of the system for handling the corona virus pandemic. The purpose of this study was to analyze the relationship between pregnant women about the covid-19 vaccine and the level of participation of pregnant women in the covid-19 vaccination programMethod : The research design used is a correlational study, with simple random sampling technique. Statistical test with Spearman Rank test.Results : Spearman Rank statistical test that the rhoxy count is 0.782 and because N>30 with = 0.05 where z count (4.56) > z table (+1.96) then Ho is rejected and Ha is accepted.. Conclution : There is a relationship between the knowledge of pregnant women about the covid-19 vaccine and the level of participation of pregnant women in the covid-19 vaccination program in Jiwut Village, Nglegok District, Blitar Regency. Keywords: Pregnant Women, Participation, Knowledge, Covid-19 Vaccine.